ASSOCIATION OF ANEMIA WITH SERUM SEX HORMONE BINDING GLOBULIN LEVELS IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME - Afzal, Hafiza Swaiba; Jafri, Syeda Rizwana; Muneeb, Amna; Zaheer, Attya; Ahmad, Ehsan; Batool, Bushra (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find association of anemia with serum sex hormone binding globulin levels in women with PCOS.Study Design: Cross sectional study.Place and Duration of Study: University of Health Sciences Lahore, from Jan 2018 to Jun 2018.Methodology: The study was conducted after approval from Ethics review committee of University of Health Sciences, Lahore. The Data was assessed by IBM-SPSS version 22. Normality of different continuous variables was checked by Shapiro-wilk test. Frequency distributions of study participants were calculated. Significance of the associations was assessed by Mann Whitney-U test and p-value